2009
DOI: 10.1080/02786820903242029
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Condensation Particle Counters for Legislated Vehicle Number Emission Measurements

Abstract: Light duty vehicle emissions legislation requires calibration and validation of Condensation Particle Counters (CPCsHowever, tests performed at JRC after the workshop found much lower counting efficiencies for tetracontane particles (almost 0 at 23 nm) and variable results for NaCl (0.6 or lower for 23 nm) indicating the importance of the generation method and the thermal treatment of the generated aerosol. Measurement issues including calibration against an electrometer or a reference CPC, the effect of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 24 publications
2
66
0
Order By: Relevance
“…The average counting efficiencies at 23 nm were 52% for C14, 49% for C16, and 48% for PAO, with the relative differences lying well within experimental uncertainty (3-5% in terms of standard deviation). This suggests that the elevated PAO efficiencies reported in previous studies (Giechaskiel et al 2009Wang et al 2010) did not originate from physicochemical interactions specific to butanol and PAO (e.g., partial solubility) that could have enhanced its activation in the CPC, since results with the two alkanes (C14 and C16) were found to be similar to PAO data. Particle contamination is also highly unlikely in the evaporation-condensation generator employed in the present study.…”
Section: Experimentally Determined Counting Efficienciessupporting
confidence: 70%
See 2 more Smart Citations
“…The average counting efficiencies at 23 nm were 52% for C14, 49% for C16, and 48% for PAO, with the relative differences lying well within experimental uncertainty (3-5% in terms of standard deviation). This suggests that the elevated PAO efficiencies reported in previous studies (Giechaskiel et al 2009Wang et al 2010) did not originate from physicochemical interactions specific to butanol and PAO (e.g., partial solubility) that could have enhanced its activation in the CPC, since results with the two alkanes (C14 and C16) were found to be similar to PAO data. Particle contamination is also highly unlikely in the evaporation-condensation generator employed in the present study.…”
Section: Experimentally Determined Counting Efficienciessupporting
confidence: 70%
“…Wang et al (2010) also reported reduced counting efficiencies of the same magnitude (reduced by 10-19% at 23 nm and 10-15% at 41 nm) for combustion aerosol standard generator (CAST) (Jing 1999) soot, oxidized silver, and polystyrene particles with respect to PAO. Moreover, Giechaskiel et al (2009) also observed similar differences between PAO and diesel soot (15% at 23 nm) or CAST soot (18% at 23 nm), at slightly elevated temperature differences (30.8…”
Section: Experimentally Determined Counting Efficienciesmentioning
confidence: 65%
See 1 more Smart Citation
“…Direct photoionization charging (Jiang et al 2007) was reported to affect the charging probabilities acquired in a recently commercialized soft X-ray neutralizer (3088 model by TSI inc.) owing to the high energies of X-rays employed (Jiang et al, 2014). Furthermore, the importance of particle shape has long been recognized (Laframboise and Chang 1977;Rogak and Flagan 1992), though it is still generally neglected (Giechaskiel et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…To this purpose, air quality experts should be able to characterize people exposure to particles metrological performances such as: linear response to particle concentrations over the full measurement range in single particle count; counting accuracy of ± 10% across the range in single particle count mode; minimum counting efficiencies at particle electrical mobility diameters of 23 ± 1 nm (50% ± 12%) and 41 ± 1 nm (> 90%). To meet these metrological requirements, the CPCs should be calibrated at least annually (Giechaskiel et al, 2009b; Commission for Europe of the United Nations, 2012).…”
Section: Introductionmentioning
confidence: 99%